COVID‐19 and the Otolaryngology Residency Match: Rising Incidence of Home Matches. (21st January 2022) - Bernstein, Jeffrey D.; Harmon, Matthew; Watson, Deborah
Abstract : Objectives/Hypothesis: To quantify the effect of the coronavirus disease 2019 (COVID‐19) pandemic upon the 2020 to 2021 residency match for Otolaryngology‐Head and Neck Surgery (OHNS). Study Design: Retrospective cohort design. Methods: Residency match outcomes for all applicants to our institution during 2020 to 2021 were collected from the National Residency Matching Program including medical school of origin and matched program. Matches were categorized as to home‐program, within‐region, or out‐of‐region and sorted by US geographic region. Matches from the 2020 to 2021 cycle were compared to those from 2019 to 2020, as well as averages and trends from match cycles 2016 to 2020. Statistical analysis included descriptive statistics and chi‐square testing. Results: During 2020 to 2021, there were 436 applicants to our single OHNS program. From 2019–2020 to 2020–2021, the match rate decreased significantly for groups studied, including: All applicants (72.0% [268/372] to 64.7% [282/436]; P = .025); all US MD Senior applicants (76.5% [254/332] to 68.9% [262/380]; P = .024); and US MD Seniors specifically without a home program (77.5% [31/40] to 56.4% [22/39]; P = .046). The match rate for US MD Seniors with a home program did not change significantly (76.4% [223/292] to 70.4% [240/341]; P = .09). From 2019–2020 to 2020–2021, the proportion of US MD seniors who matched to home‐program increased significantly (22.0% [49/223] to 30.0% [72/240]; P = .05). Conclusion: The COVID‐19 pandemic saw high volumes of OHNS applicants with an overall decreased rate of matching compared to previous years. These changes particularly affected applicants without home programs. Home‐program matching increased significantly, likely as a consequence of the limitations placed on in‐person away experiences including interviews. Laryngoscope, 132:1934–1938, 2022